THE EMERGING ROLE OF SERRATIOPEPTIDASE IN ORAL SURGERY: LITERATURE UPDATE - Kumar Mp, Santhosh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Serratiopeptidase, a proteolytic enzyme derived from Serratia E-15 species enterobacteria, is widely used in medical field for its anti-inflammatory, anti-edemic properties, and analgesic properties. It is being used commonly in various specialties such as orthopedics, otolaryngology, gynecology, surgery, pulmonology, ophthalmology, and dentistry. Research has shown that serratiopeptidase is the most effective anti-inflammatory agent compared to other enzyme preparations. This article reviews the efficacy, safety, and applications of serratiopeptidase in oral surgery. This article also discusses the mechanism of action of serratiopeptidase, its contraindications and complications. From the recently published literature, it is clear that the role of serratiopeptidase as a therapeutic agent in oral and maxillofacial surgery is expanding and they hold a promising future as a broad-spectrum anti-inflammatory drug with minimal side effects and complications. Further, research will broaden their applications in the field of medicine and dentistry.